CDX-585, a Bispecific Antibody with Dual Targeting of ILT4 and PD-1 Checkpoint Pathways - Michael B. Murphy; Laura Vitale; Shukai Xia; Zeyu Peng; Thomas O’Neill; Jay Lillquist; Anna Wasiuk; Jeff Weidlick; Jenifer Widger; Laura Mills-Chen; Andrea Crocker; Colleen Patterson; et al. (Immuno, 2023)
Immunoglobulin-like transcript 4 (ILT4) is an immunosuppressive molecule predominantly expressed on myeloid cells. Recent studies combining ILT4 suppression with programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) blockade have shown promising signs of activity in immune checkpoint inhibitor refractory patients. We theorized that coupling ILT4 and PD-1/PD-L1 blockade in a bispecific antibody (bsAb) may provide greater immune activating properties than combining the individual mAbs due to enhanced bridging of APCs to T cells. To test this approach, we developed CDX-585, a tetravalent ILT4xPD-1 IgG1-scFv bsAb from novel PD-1 and ILT-4 mAbs. CDX-585 is a potent antagonist of both PD-1 and ILT4. CDX-585 promotes M1 macrophage polarization and enhances pro-inflammatory cytokine secretion in response to lipopolysaccharide or CD40 agonist mAb treatment. In mixed lymphocyte reaction (MLR) assays, CDX-585 is more potent than the combination of parental antibodies. In a humanized NCG mouse SK-MEL-5 tumor model, CDX-585 exhibits greater antitumor activity than the combination of parental mAbs. A pilot study of CDX-585 in cynomolgus macaques confirmed a mAb-like pharmacokinetic profile without noted toxicities. These studies demonstrate that CDX-585 effectively combines ILT4 and the PD-1 blockade into one molecule that is more potent than the combination of the parental antibodies, providing the rationale to advance this bsAb into clinical studies.